An Analysis of Patient Perceptions and Expectations to Dental Implants: Is There a Significant Effect on Long-Term Satisfaction Levels? - Shane J. J. McCrea (International Journal of Dentistry)
Here we present an analysis of patient perceptions and expectations to dental implant placement and their prosthetic reconstruction, to then consider whether they have an effect on long-term satisfaction levels. A Post-Treatment Completion Questionnaire was designed to analyse whether patient satisfaction is influenced by age and/or gender; has an effect on patient-reported self-confidence levels; contributes to increased levels of oral hygiene; provides further insight into the average pain levels during and after the surgical intervention; or influences further acceptance of dental implant surgery. And then whether relationships exist between any of these factors. 182 consecutive patients completed the survey: 68 males and 114 females (age mean 64.68 years ± 11.23 SD); the average number of months since treatment completion was 37.4 (males) and 62.6 (females). There is a significant relationship between comfort rating and “how well informed” the patient was (p=0.015). A significantly positive relationship exists between “considering dental implants in the future” and “overall experience” (p=0.001). A significantly positive relationship exists between “overall satisfaction with appearance” and “satisfaction with comfort” (p=0.011). A significant relationship exists between “overall satisfaction with appearance,” “satisfaction with comfort,” and “overall satisfaction with experience” (p=0.001). The results amplify the need to transmit logical, truthful information to patients when dental implant treatment is being considered. The “fully informed” patient will have realistic expectations that lead to high degrees of satisfaction.